2016
DOI: 10.1002/hipo.22607
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of glutamatergic terminals (VGLUT1) driven by Aβ in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized phenotypically by memory impairment, histologically by accumulation of pTau and β-amyloid peptide and morphologically by a loss of nerve terminals in cortical and hippocampal regions. As glutamate is the principle excitatory neurotransmitter of the central nervous system (CNS), the glutamatergic system may play an important role in AD. To date, not many studies have addressed the deleterious effects of Aβ on glutamatergic terminals; therefore the aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 55 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…Also in retinitis pigmentosa, alterations in synapse and glutamate receptors are supposed to take part in its pathomechanism [ 71 , 72 , 73 ]. In addition to synapse alterations occurring in ocular diseases, they also play a decisive role in other diseases, especially in relation to Alzheimer’s disease [ 74 , 75 , 76 , 77 ], as reduced levels of VGluT1 heighten beta amyloid-induced neuroinflammation and affect synaptic plasticity [ 78 ]. Likewise, in an animal model that examined the impact of apolipoprotein E4, lower levels of VGluT1 were noted in retinas [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in retinitis pigmentosa, alterations in synapse and glutamate receptors are supposed to take part in its pathomechanism [ 71 , 72 , 73 ]. In addition to synapse alterations occurring in ocular diseases, they also play a decisive role in other diseases, especially in relation to Alzheimer’s disease [ 74 , 75 , 76 , 77 ], as reduced levels of VGluT1 heighten beta amyloid-induced neuroinflammation and affect synaptic plasticity [ 78 ]. Likewise, in an animal model that examined the impact of apolipoprotein E4, lower levels of VGluT1 were noted in retinas [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, does not examine the cause for this accumulation, and does not offer any insight into the potential mechanisms involved in this change. This accumulation of Aβ in AD has been shown to result in selective decline in VGluT1 expression (Rodriguez-Perdigon et al, 2016). Rodríguez-Moreno and Lerma (1998) noted a reduction in both glutamatergic terminals and VGluT1 levels in hippocampal cell cultures exposed to Aβ, with intracerebroventricular administration of Aβ 1−42 resulting in altered synaptic plasticity and neuroinflammation.…”
Section: Vglut Expression Alterations 3 Days Post-aβ Injectionmentioning
confidence: 99%
“…Furthermore, Aβ could interact with the glutamatergic systems in a number of ways. Studies in transgene mouse models and AD brains have found that plaque load is correlated with lower expressions of VGLUT1 [ 47 ]. The model further assumes linear effects of therapeutic interventions by amyloid-lowering agents.…”
Section: Discussionmentioning
confidence: 99%